Analisa pengaruh persepsi nasabah terhadap keputusan memilih dan kepuasan nasabah Cash Management System tahun 2013-2016 - Eros Khairun Oktavianto; Wilfridus B. Elu (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2018)
This research was performed in order to analyze the effect of customers Perception (X) against Decision to Choose (Y), Decision to Choose (Y) against customers satisfaction (Z), and customers Perception (X) against customers satisfaction (Z) of CMS PT Bank DKI. Methodology research as the sample used simple random sampling through questionnaires with the following criteria: (1) Have an account with at least one year; (2) Account was active; (3) Government Customers and Non Government Customers of PT Bank DKI. The research data obtained directly through a questionnaires to the selected respondents. The selected respondents as much as 70 respondents. Analysis technique used is Structural Equation Modelling (SEM). Results of analysis used SPSS version 23 and AMOS 23 shows that: (1) Customer perception have positive effect against customers Decision to Choose of CMS PT Bank DKI is amounting to 1.713. (2) Customers decision to Choose have positive effect against customer satisfaction of CMS PT Bank DKI was amounting to 0.564. (3) Customer perception have positive effect against customer satisfaction of CMS PT Bank DKI is amounting to 0.989. CMS Bank DKI product must be promoted well by management, variations of internet banking features also need to be adjusted to the needs of customers, and benchmarking of products and services was done as a strategy to open insights and product competencies between Banks.